Energy harvesting and forced convective heat transfer features of multiple slot jet impingement cooling of partly elastic flat and curved surfaces having double piezo-energy harvesters - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Ltd, 2025)
In the present study, a novel cooling system with multiple slot jet impingement and piezo-electric energy harvester (PE-EH) is proposed. The target surface is partly elastic while both curved and flat surfaces are considered in the turbulent flow regime. The PE-EHs are mounted below the elastic part of the hot surface. Finite element method with arbitrary Lagrangian-Eulerian (ALE) formulation is used. The numerical analysis is carried out taking into account both flat and curved surfaces for various values of the jet flow Reynolds number (Re, between 6000 and 30000), jet inlet to target plate distance (Hj between 2wj and 6wj), and distance between the slots (sj between 3wj and 7wj). At the maximum Re, the cooling performance enhancement factor increases to 5.89 for the curved wall configuration and 4.3 for the flat wall layout. The findings demonstrate that the generated power and deflections are significantly impacted by the jet flow rate. As the jet to target plate distance increases from minimum to maximum for the flat situation, the average Nu decreases by roughly 12%. For curved and flat wall layouts, the cooling performance changes by 26% and 4.5% for varying slot-slot distances, respectively. Changing the slot-slot distance results in a 15% increase in generated power in the flat case and a 22% increase in the curved case. For average heat transfer and generated power, a polynomial type correlation is developed, taking into account variations in slot-plate and slot-slot distances. The development and enhancement of studies pertaining to electronic cooling, drying, and various heat transfer devices, as well as self-sustaining power production equipment, can benefit from the findings of this study. © 2025 The Author(s)
Keywords: Curved elastic; Energy harvester; Finite element method; Multiple jet impingement; Piezo-electric; Turbulent flow